1993
DOI: 10.1177/095632029300400206
|View full text |Cite
|
Sign up to set email alerts
|

Footprinting Studies on the Sequence-Selective Binding of Tilorone to DNA

Abstract: DNAase I footprinting has been used to investigate sequence selectivity in the binding of the antiviral fluorenone derivative tilorone to DNA. Using the 160 base pair EcoRI-AvaI tyr T restriction fragment and the 166 base pair EcoRI-BstEII ptyr 2 restriction fragment, obtained respectively from the Plasmids pKMΔ-98 and pMLB 1048, it is shown that tilorone binds to DNA with a preference for alternating purine-pyrimidine sequences. Enhancement of DNAase I cleavage occurs at homopolymeric A and T stretches and, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

1993
1993
2004
2004

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 71 publications
(64 reference statements)
1
2
0
Order By: Relevance
“…For tilorone, the AT preference initially proposed on the basis of theoretical calculations (Chen et al, 1988) and spectroscopic measurements (Chandra & Woltersdorf, 1976) did not hold up when foot printing experiments were performed. In agreement with Sturm (198 2), we found that tilorone binds best to alternating purine-pyrimidine sequences which can contain both AT and GC base pairs (Bailly & Waring, 1993). For amiloride, the cleavage inhibition assays clearly evidenced the AT preference (Bailly et al, 1993a), but the chemical structure of this drug, a pyrazine derivative, is totally different from that of the thioxanthenones, not least in the lack of a polycyclic aromatic ring system.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…For tilorone, the AT preference initially proposed on the basis of theoretical calculations (Chen et al, 1988) and spectroscopic measurements (Chandra & Woltersdorf, 1976) did not hold up when foot printing experiments were performed. In agreement with Sturm (198 2), we found that tilorone binds best to alternating purine-pyrimidine sequences which can contain both AT and GC base pairs (Bailly & Waring, 1993). For amiloride, the cleavage inhibition assays clearly evidenced the AT preference (Bailly et al, 1993a), but the chemical structure of this drug, a pyrazine derivative, is totally different from that of the thioxanthenones, not least in the lack of a polycyclic aromatic ring system.…”
Section: Discussionsupporting
confidence: 87%
“…It has been widely used to detect unusual DNA structures (Johnston & Rich, 1985;McLean & Wells, 1988;Palecek et al, 1989). In pharmacology, it has been applied with success to examine the structural changes in DNA induced by binding of mono-and bis-intercalating agents (Mclean & Waring, 1988;McLean etal., 1989;Bailly & Waring, 1993). The osmium tetroxidebis(pyridine) complex attacks the 5,6 double bond of pyrimidines in the major groove, most particularly at thymine residues.…”
Section: Resultsmentioning
confidence: 99%
“…For instance, they could influence the folding of the DNA [203], induce cytokine-operation in general, and interferon-activities (endogenous reactions see also chapter 4.2.) in particular [314][315][316][317], and are capable of inhibiting both reverse transcriptases and telomerases [162,[317][318][319][320][321][322][323]; see Fig. (10).…”
Section: Supramolecular Relationshipmentioning
confidence: 99%